2015
DOI: 10.12957/reuerj.2015.16498
|View full text |Cite
|
Sign up to set email alerts
|

Categorias de autocuidado entre pessoas idosas com diabetes: estudo sociopoético

Abstract: RESUMO: Teve-se como objetivo identificar as categorias de autocuidado apresentadas por pessoas idosas com diabetes, considerando suas dimensões física, mental e espiritual. Método sociopoético, aplicando as fases do grupo-pesquisador formado por 10 participantes da pesquisa e curso de autocuidado, que desenvolveram a técnica artística Vivência do corpo como território mínimo, utilizando o desenho livre, em 2012, no Rio de Janeiro-Brasil. Nos resultados ressaltam-se as categorias: dificuldades de autocontrole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
1
1
0
2
Order By: Relevance
“…20 A study conducted in the city of São Paulo found that the presence of hypertension increases by 39% the chance of elderly people becoming dependent for the BADLs and that heart disease, arthropathy, and lung disease increase by 82%, 59%, and 50%, respectively, the chances of these individuals developing dependence. 19 Diabetes mellitus alone did not have a statistically significant relationship with dependence for the activities of daily livin, 14 corroborating with the data described in Table 2.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…20 A study conducted in the city of São Paulo found that the presence of hypertension increases by 39% the chance of elderly people becoming dependent for the BADLs and that heart disease, arthropathy, and lung disease increase by 82%, 59%, and 50%, respectively, the chances of these individuals developing dependence. 19 Diabetes mellitus alone did not have a statistically significant relationship with dependence for the activities of daily livin, 14 corroborating with the data described in Table 2.…”
Section: Discussionsupporting
confidence: 79%
“…Contrary to these data, it is worth highlighting a survey conducted with elderly people in the city of São Paulo, which showed different results when concluding that the highest chance, about 1.9 times, of developing functional disability was among individuals aged 65 to 69 years old. 19 The reduction in the functional capacity is directly associated with the presence of hypertension, cardiovascular disease and stroke sequela. 20 A study conducted in the city of São Paulo found that the presence of hypertension increases by 39% the chance of elderly people becoming dependent for the BADLs and that heart disease, arthropathy, and lung disease increase by 82%, 59%, and 50%, respectively, the chances of these individuals developing dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Nesse contexto, o autocuidado em saúde é definido como as medidas que cada pessoa, de forma ciplinares, para atuarem junto às pessoas, visando ao ensino/aprendizagem do autocuidado, para viver com bem-estar, mesmo em situações limitantes devido ao adoecimento 21 .…”
Section: Características Individuais N % Sexounclassified
“…O investimento nas políticas públicas de saúde voltadas para a população, referentes à prevenção de doenças, pode contribuir para a promoção da saúde, aqui entendida como autocuidado, desde a faixa etária infantil e da adolescência 21 .…”
Section: Conclusãounclassified